Viruses : essential agents of life - Witzany, Gunther (Springer, 2012)
"Viruses are now considered to play major roles in the evolution of life. Because they have genes that are not found in any cellular organism they seem to be remnants of early stages of life on earth. Besides their disease causing features and actions as genetic parasites viruses have lifestyles that are clearly symbiotic and even symbiogenetic. Increasing empirical data suggest that some viruses such as endogenous retroviruses and non-retroviral RNA viruses and even DNA viruses prefer cellular genomes as habitat. They determine genetic host (group) identity and genetic host features. Viruses and virus-related modules such as mobile genetic elements and other repeat sequences identified in intronic regions of host genomes play important roles in gene regulation and genetic content (re)arrangement. This book exemplifies some astonishing key features of viruses acting as essential agents of life."-- Publisher